Paper girls (2015), volume 4 ebook - Vaughan, Brian K. (Paper Girls (2015), 2018)
The mind-bending, time-warping adventure from BRIAN K. VAUGHAN and CLIFF CHIANG continues as intrepid newspaper deliverer Tiffany is launched from the prehistoric past into the year 2000! In this harrowing version of our past, Y2K was even more of a cataclysm than experts feared, and the only person who can save the future is a 12-year-old girl from 1988. Collects PAPER GIRLS #16-20. Author: Brian K. Vaughan. Illustrator: Cliff Chiang, Matt Wilson . 2018 Brian K Vaughan & Cliff Chang.